Social Construction of Quality in Moscow Dental Market - Berdysheva, Elena (Journal of Economic Sociology, 2014)
The acts of purchase and sale cannot be realized without product quality evaluation and price “reasonableness” analysis. In this respect, the processes of definition, stabilization and institutionalization of categories and revealing the contents of market commodities turn out to be of key importance in the framework of contemporary markets. This article reconstructs categories that operationalize the content and quality of Moscow dental market health services in an attempt to reveal the effective social order. The article is to depict clinics’ marketing efforts directed at their services’ qualifications and to represent ideas about quality and its determinants, as used by different actors (doctors, clinic managers and patients). Special attention is given to the way patients evaluate medical service quality when choosing a clinic. With data from clinic websites and in-depth interviews with market participants, it can be concluded that there is no quality criteria consensus in the studied market. According to respondents with different backgrounds, the success of any given dental treatment depends on the professionalism of the doctor. The latter is interpreted as the motivation of the doctor towards professionalism rather than his or her skill and experience level. As far as doctors are concerned, the quality of dental services requires an integrated approach to treatment contributing to a person’s general health. Conversely, patients will often only visit a clinic when their dental problems can no longer be ignored, and they want a quick solution, permanently and in line with modern ideas about how healthy teeth should look. No matter how much effort clinics make to explain their competitive advantages, customers tend to base their qualitative judgments on the opinions of members of their reference group, people who had already experienced the quality of dental services through their body and wallet. Although, the investments clinics make in the qualification of quality in the market are not in vain. Patients use cognitive categories obtained from this discourse when asking for details about the clinic from friends and if they doubt how reasonable the cost of the treatment is. Thus, the conventional lexicon of Moscow’s dental market is defined by parameters that comprise dental services and constitute their quality.